TANDATANGAN DIGITAL SEBAGAI SOLUSI TEKNOLOGI INFORMASI DAN KOMUNIKASI (TIK) HIJAU: SEBUAH KAJIAN LITERATUR (DIGITAL SIGNATURE AS GREEN INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) SOLUTION: A REVIEW PAPER) - Abraham, Firda Zulivia; Santosa, Paulus Insap; Winarno, Wing Wahyu (Kementerian Komunikasi dan Informatika R.I., 2018)
Abstract The presence of Information and Communication Technology (ICT) can be a solution to environment issues, one of the concepts about environment-friendly of ICTs is a Green ICT. Digital Signature in Indonesia regulated in Government Regulation No.82/2012 About System Implementation and Electronic Transaction, thats works to authentification tools and verification. By implementing of Green ICT, it’s expected that the use of media such as excess paper in office will be minimized. This study looking for Green ICT solution using the Digital Signature. With the existing theory, it is expected that the implementation of Digital Signature can reduce the use of paper in the office and maximize the concept of e-Government. However, implementation of e-Government with the technology increasing the use of paper and the use of digital signature technology with high-tech encryption is felt to burden the organization, it is not same way with objective of e-Government, a budget efficiency. Therefore Digital Signature with PKCS#12 method which are issued officially by the government expected to increase paper reduction. PKCS#12 method in addition to not requiring its own infrastructure, the use of the method also does not require a lot of money to funding the Digital Signature system.Abstrak Kehadiran Teknologi Informasi dan Komunikasi (TIK) menjadi sebuah solusi mengenai isu ramah lingkungan, salah satu konsep tentang TIK yang ramah lingkungan adalah Green Information and Communication Technology (Green ICT). Tanda Tangan Digital di Indonesia diatur dalam Peraturan Pemerintah No.82 Tahun 2012 Tentang Penyelenggaraan Sistem dan Transaksi Elektronik, yang berfungsi sebagai alat autentifikasi dan verifikasi. Dengan menerapkan Green ICT, diharapkan penggunaan media seperti kertas berlebih di lingkungan perkantoran akan semakin diminimalisir. Penelitian ini ditulis sebagai kajian dari sebuah sistem pendukung Green ICT, yaitu Tanda Tangan Digital (TTD). Dengan teori yang sudah ada diharapkan penerapan TTD dapat mengurangi penggunaan kertas di lingkungan perkantoran atau lebih memaksimalkan konsep e-Government. Penggunaan TTD dengan metode PKCS#12 diharapkan dapat meningkatkan lagi pengurangan kertas, selain tidak memerlukan infrastruktur tersendiri, penggunaan dengan metode tersebut juga tidak membutuhkan biaya yang banyak